Analysis of Language Errors in The Level of Phonology in The Movie Habibie and Ainun 3 - Bukhari, Ahmad Bukhari Nasution; Diva Azzurra Putri Rialni; Nurul Hijrah; Safinatul Hasanah Harahap (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to analyze phonological errors in the film Habibie and Ainun 3. The research method used in this research is a qualitative descriptive method. The qualitative descriptive method is fact-finding in the form of a systematic description of data and prioritizing the weight of data and research evidence, even though the research does not use calculations. The data collection technique is by watching films and recording the phonological errors spoken by the actors in the film. There are 20 phonological errors in the film Habibie and Ainun 3. These errors are found in the phonology area of ​​changing the pronunciation of phonemes with 11 errors, the area of ​​phoneme changes with 4 errors, the addition of phonemes with 2 errors, and the area of ​​changing diphthong sounds into single phonemes with 3 errors. Keywords: film, Habibie and Ainun, phonology, linguistics